The Design of Quick Response Code Incoming Information Systems at POS SPP Bandung Based on Android - Andhika Saputra; Edi Suharto; Mochamad Isryn Winandi (Politeknik Piksi Ganesha Indonesia, 2022)
This study aims to analyze, design, and build an information system at POS SPP Bandung. The authors obtained the necessary data using observation, interviews, and literature studies from several previous studies. Based on employee observations and interviews, the system in POS SPP incoming division was less efficient, because it took two employees to run the item scan system. The goal to be achieved is that the information system that we have designed can help the process of receiving goods or items to be more accurate and faster. And as it only requires one employee to carry out the process of receiving goods, making it more effective and efficient. Therefore, in this study, an Android-based item input information system design was made using UML and implemented with the Java programming language and MySQL as a database and quick response code feature for the scanning process.